Freshwater Microplastics Emerging Environmental Contaminants? - Wagner, Martin; Lambert, Scott; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book is open access under a CC BY 4.0 license. This volume focuses on microscopic plastic debris, also referred to as microplastics, which have been detected in aquatic environments around the globe and have accordingly raised serious concerns. The book explores whether microplastics represent emerging contaminants in freshwater systems, an area that remains underrepresented to date. Given the complexity of the issue, the book covers the current state-of-research on microplastics in rivers and lakes, including analytical aspects, environmental concentrations and sources, modelling approaches, interactions with biota, and ecological implications. To provide a broader perspective, the book also discusses lessons learned from nanomaterials and the implications of plastic debris for regulation, politics, economy, and society. In a research field that is rapidly evolving, it offers a solid overview for environmental chemists, engineers, and toxicologists, as well as water managers and policy-makers.
Microplastics are contaminants of emerging concern in freshwater environments: an overview -- Aquatic ecotoxicity of microplastics and nanoplastics - lessons learned from engineered nanomaterials -- Analysis, Occurrence, and Degradation of Microplastics in the Aqueous Environment -- Sources and fate of microplastics in urban areas: a focus on Paris Megacity -- Microplastic pollution in inland waters focusing on Asia -- Microplastics in inland African waters: presence, sources and fate -- Modelling the fate and transport of plastic debris in fresh waters. Review and guidance -- Interactions of microplastics with freshwater biota -- Microplastic-associated Biofilms: A Comparison of Freshwater and Marine Environments -- Risk perception of plastic pollution: Importance of stakeholder involvement and citizen science -- Understanding the Risks of Microplastics. A Social-Ecological Risk Perspective -- Freshwater microplastics: challenges for regulation and management -- Microplastic: What are the solutions?
Keywords: Environmental chemistry; Water; Hydrology; Geochemistry; Analytical chemistry; Environmental Chemistry; Water; Geochemistry; Analytical Chemistry